On the dynamic behavior of the current in the condenser of a boost converter controlled with ZAD - Darío Del Cristo Vergara Perez; Simeón Casanova Trujillo; Fredy Edimer Hoyos Velasco (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
In this paper, an analytical and numerical study is conducted on the dynamics of the current in the condenser of a boost converter controlled with ZAD, using a pulse PWM to the symmetric center. A stability analysis of periodic 1T-orbits was made by the analytical calculation of the eigenvalues of the Jacobian matrix of the dynamic system, where the presence of flip and Neimar–Sacker-type bifurcations was determined. The presence of chaos, which is controlled by ZAD and FPIC techniques, is shown from the analysis of Lyapunov exponents.